Social Capital in the Reorientation of Location Decisions - Korenik, Stanisław (Kapitał społeczny w reorientacji decyzji lokalizacyjnych, 2023)
The current turbulences occurring in the world economy have resulted in various transformations, often of a revolutionary nature. The reorientation of behaviour has resulted, among others, in the shortening of supply chains and changes in location policies, which necessitate the search for new places to relocate capital. Of particular importance in this process are regions in which there is a developed social capital featuring a high level of adaptation both to the conditions of the digital economy, and to the modern form of organisation in which flexible cooperation dominates.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 40-47
Keywords: social capital; location; digital economy; endogenisation; region; kapitał społeczny; lokalizacja; gospodarka cyfrowa; endogenizacja